Nephron Progenitor But Not Stromal Progenitor Cells Give Rise to Wilms Tumors in Mouse Models with β-Catenin Activation or Wt1 Ablation and Igf2 Upregulation - Le Huang; Sharada Mokkapati; Qianghua Hu; E. Cristy Ruteshouser; M. John Hicks; Vicki Huff (Neoplasia: An International Journal for Oncology Research, 2016)
Wilms tumor, a common childhood tumor of the kidney, is thought to arise from undifferentiated renal mesenchyme. Variable tumor histology and the identification of tumor subsets displaying different gene expression profiles suggest that tumors may arise at different stages of mesenchyme differentiation and that this ontogenic variability impacts tumor pathology, biology, and clinical outcome. To test the tumorigenic potential of different cell types in the developing kidney, we used kidney progenitor-specific Cre recombinase alleles to introduce Wt1 and Ctnnb1 mutations, two alterations observed in Wilms tumor, into embryonic mouse kidney, with and without biallelic Igf2 expression, another alteration that is observed in a majority of tumors. Use of a Cre allele that targets nephron progenitors to introduce a Ctnnb1 mutation that stabilizes β-catenin resulted in the development of tumors with a predominant epithelial histology and a gene expression profile in which genes characteristic of early renal mesenchyme were not expressed. Nephron progenitors with Wt1 ablation and Igf2 biallelic expression were also tumorigenic but displayed a more triphasic histology and expressed early metanephric mesenchyme genes. In contrast, the targeting of these genetic alterations to stromal progenitors did not result in tumors. These data demonstrate that committed nephron progenitors can give rise to Wilms tumors and that committed stromal progenitors are less tumorigenic, suggesting that human Wilms tumors that display a predominantly stromal histology arise from mesenchyme before commitment to a stromal lineage.